Hyperinflammation after anti-SARS-CoV-2 mRNA/DNA vaccines successfully treated with anakinra: Case series and literature review. Issue 4 (February 2022) - Bindoli, Sara; Giollo, Alessandro; Galozzi, Paola; Doria, Andrea; Sfriso, Paolo
The current SARS-CoV-2 pandemic diffused worldwide has encouraged the rapid development of vaccines to counter the spread of the virus. At present in Italy, 75.01% of the population completed the vaccination course (AIFA.gov.it) and very few adverse events have been recorded by now. Side-effects related to a theoretical over-reaction of the immune system in response to vaccines administration have been described, and the possibility that an autoimmune or a hyperinflammatory condition may occur was recently observed. Herein, we report four cases of hyperinflammatory syndrome with features indicative of Adult-onset Still's disease (AOSD) and macrophage activation syndrome (MAS), occurred after anti-SARS-CoV-2 vaccine injection and seen at our Unit between March and May 2021. Since interleukin (IL)-1 is one of the pivotal cytokines involved in AOSD pathogenesis, the inhibition of IL-1 is crucial in ameliorating the clinical symptoms of those patients. Moreover, it has been highlighted the central role of IL-1 as a hallmark of the hyperinflammatory status elicited by SARS-CoV-2 infection. In this case series, we successfully employed the IL-1 receptor antagonist anakinra to curb the cytokine release likely unleashed by the vaccine stimulation in potentially predisposed subjects. We also made a literature search to detect other patients with hyperinflammation temporally related to vaccines injection who benefited from IL-1 inhibition, while other AOSD/MAS-like described syndromes improved with other immunomodulatory strategies.